Automated subsystem for processing and analyzing seismic data from the Carpathian region - Verbytskyi, S. T.; Verbytskyi, Yu. T.; Stetskiv, O. T.; Nischimenko, I. M. (S. Subbotin Institute of Geophysics of the NAS of Ukraine, 2019)
It is presented the description of a system of seismic observations of the Carpathian region, the scheme of work of the center of collecting and processing of seismic information, the concept of regional base of seismological data of the Carpathian region. The principles of use of a control system of the database as the main instrument of preservation and manipulation of seismological information are shown. Development and deployment of a number of software which significantly improve process of input, editing, the analysis, graphical and documentary representation of seismological information is described. Work of a subsystem of processing and the analysis of data of the center of processing and storage of seismological data of a system of seismic observations of the Carpathian region is considered. Work of an automatic discernment of seismic events on the basis of the developed module of the program associator “SEISMIC ASSOCIATOR” is shown. Are described the interface of the developed software package on processing and the analysis of seismic data and its modules. The developed means of the visual analysis and correction of parameters of a seismic event are presented. The possibility of obtaining reporting documentation which allows to create seismological bulletins for the chosen time term of observations and also creation of the card of arrangement of epicenters of the seismic events selected according to particular criteria and displays of the received results by means of service “Google maps” is realized. The possibility of comparison of epicenters of seismic events to arrangement of local the geological faults is realized. It is shown as the automated subsystem of processing and the analysis of network of seismic observations of the Carpathian region of processing allows to carry out the complex analysis of seismological information and also in process of accumulation of data gives the chance more precisely to estimate regional regularities, to specify local hodographs of seismic waves, to find out power dependences in the explored region.